Indeks desa zakat (IDZ) social mapping against zakat community development (ZCD) program for optimizing zakat funds empowerment - Nurida Isnaeni; Ridhwan Ridhwan; Sigit Indrawijaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research is entitled Social Mapping of the Zakat Village Index (IDZ) on the Zakat Community Development (ZCD) Program for Optimizing the Empowerment of Zakat Funds. The purpose of this research is to find out and analyze the right village to be the object of calculating the Zakat Village Index. As well as knowing and analyzing the priority scale of a village in receiving zakat funds using the Zakat Village Index Calculation method. The method used is a quantitative method, by collecting data based on available databases such as BAZNAS and BPS. The analytical tool used in this study is the Zakat Village Index (IDZ) by calculating the multi-stage weighted index method. The results showed that three villages deserved to be the object of the calculation of the Zakat Village Index. namely Pematang Rahim Village, Bukit Tempurung Village and Sungai Beras Village. The priority scale for villages to receive zakat funds in the Zakat Community Development program is determined by calculating the Zakat Village Index, which is adjusted to the Score Range. The closer the IDZ value is to 1, the more villages are not prioritized. On the other hand, the closer IDZ is to 0, and the village is prioritized for assistance. The results of the calculation of the Zakat Village Index in the three villages used as research objects show that Pematang Rahim with an IDZ value of 0.56, shell hills of 0.50, and Sungai Beras village of 0.56 so that it can be concluded that the three villages can be considered for assistance